Synthesis, anti-aging and mechanism of magnolol derivatives - Pang, Xinxin; Mao, Li; Ye, Danyang; Wang, Wenqi; Yang, Hongliu; Fan, Xiaoxiao; Yang, Yuping; Su, Zhijun; Ma, Tao; Sun, Mingqian; Liu, Yonggang (Frontiers in Chemistry, 2023)
Magnolol (M), a biphenol containing an allyl side chain, is one of the main active ingredients in the antioxidant and anti-aging properties of Magnolia. In order to enhance the antioxidant activity of magnolol, magnolol was structurally modified in this experiment, and a total of 12 magnolol derivatives were obtained by structural modification of different active sites of magnolol. A preliminary investigation of the anti-aging effect of magnolol derivatives based on the Caenorhabditis elegans (C. elegans）model revealed that M27 had the best anti-aging effect. To investigate the effect of M27 on senescence and the potential mechanism of action, we investigated the effect of M27 on senescence in C. elegans. Our results indicate that M27 prolongs the lifespan of C. elegans. Meanwhile, M27 promotes healthy lifespan of C. elegans. by improving pharyngeal pumping ability and reducing lipofuscin accumulation in C. elegans.M27 increased resistance to high temperature and oxidative stress in C. elegans by reducing ROS. Application of M27 on the transgenic mutant TJ356 induced transfer of the transcription factor daf-16 from the cytoplasm to the nucleus and upregulated the expression of sod-3 (a gene downstream of daf-16) in C. elegans. Furthermore, M27 did not extend the lifespan of daf-16, age-1, daf-2 and hsp-16.2 mutants, suggesting that these genetic pathways are involved in mediating the antioxidant and anti-aging effects of M27.